Internet connectivity disruption in Egypt (Egypt) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Egypt. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: EG-2026-0186. Severity: critical. Confidence: 67%